Effect of rosuvastatin or its combination with omega-3 fatty acids on circulating CD34+ progenitor cells and on endothelial colony formation in patients with mixed dyslipidaemia. (August 2016) - Chantzichristos, Vasileios G.; Agouridis, Aris P.; Moutzouri, Elisavet; Stellos, Konstantinos; Elisaf, Moses S.; Tselepis, Alexandros D.
Abstract: Background and aims: Hypercholesterolaemia is associated with a reduced number of circulating progenitor cells, a defect that is restored by statin therapy. We studied the effect of rosuvastatin monotherapy or its combination with omega-3 polyunsaturated fatty acids (ω-3 PUFAs) on progenitor cell number and function in patients with mixed dyslipidaemia. Methods: Fifty patients with mixed dyslipidaemia and fifty-five normolipidaemic, apparently healthy, age- and sex-matched volunteers participated in the study. Patients were randomized to receive a daily dose of either 40 mg rosuvastatin (R group, n = 26) or 10 mg rosuvastatin plus 2 g of ω-3 PUFAs (R + O group, n = 24). The number of circulating CD34 + and CD34 + /KDR + progenitor cells as well as the number of colony-forming units-endothelial cells (CFU-ECs) at 10 days of culture were assessed at baseline and 3 months post-treatment. Results: The number of CD34 + and CD34 + /KDR + cells per 10, 000 leukocytes as well as the number of CFU-ECs were significantly lower in both patient groups compared with healthy volunteers (all p = 0.03). A 3-month treatment with either R or R + O significantly increased circulating CD34 + and CD34 + /KDR + cells as well as the number of CFU-ECs compared with baseline (all p = 0.03). Importantly, the increase in the above parameters was inversely correlated with therapy-induced reduction in lipid parameters in both patient groups. Conclusions: Patients with mixed dyslipidaemia exhibit low numbers of circulating CD34 + and CD34 + /KDR + cells as well as CFU-ECs in culture, a defect restored by 3-month treatment with either high-rosuvastatin dose or a combination of low-rosuvastatin dose with ω-3 PUFAs. The pathophysiological meaning of our results regarding the increased cardiovascular risk in these patients remains to be established. Highlights: Patients have lower number of progenitor cells and colonies compared with controls. The numbers of cell parameters at baseline are inversely correlated with lipid levels. Rosuvastatin or its combination with ω-3 PUFAs increases the cell parameters. The increase in the number of cells is inversely associated with therapy-induced decrease in lipids.